Apoptosis and Engulfment by Bronchial Epithelial Cells. Implications for Allergic Airway Inflammation - Penberthy, Kristen K. (Ann Am Thorac Soc, 2014)
Insult or injury to the lung epithelial cells from pathogens, pollutants, and allergens can initiate the process of apoptotic cell death. Although “Creola bodies,” which are clusters of uncleared, apoptotic, epithelial cells, have been seen in the sputum of patients with asthma, the clearance of these dying epithelial cells and the consequence of failed clearance in the airway have not been directly addressed. We have observed that bronchial epithelial cells efficiently engulf their apoptotic neighbors and produce antiinflammatory cytokines when engulfing apoptotic cells. Furthermore, when the phagocytic capacity of bronchial epithelial cells was impaired, mice developed severe, IL-33–dependent, allergic airway inflammation. This inflammation could be ameliorated by exogenous administration of the antiinflammatory cytokine IL-10. Our data suggest that the process of apoptotic cell engulfment is a mechanism by which bronchial epithelial cells regulate the inflammatory environment within the lung. Collectively, these studies suggest that impaired engulfment pathways in airway epithelial cells can contribute to allergic airway inflammation and that targeting these pathways may be of benefit in human airway inflammation.